The Effect of Coal and Biomass on the Generation of Fly Ash and Bottom Ash at the Coal-Fired Power Plant Asam Asam Unit 1-4, South Kalimantan - Abidin, Khoirul; Chaerul, Mochammad (Applied Research in Science and Technology, 2025)
Background: One of the main environmental challenges in Coal-Fired Power Plant (CFPP) operations is the large amount of Fly Ash and Bottom Ash (FABA) produced, which creates significant waste management issues. Reducing FABA production through biomass co-firing has become a potential solution, yet its effectiveness in actual operations remains underexplored. Asam Asam Power Plant Unit 1–4, with a capacity of 4 × 65 MW in South Kalimantan, is one of the power plants that utilize sawdust biomass in its operations.Aims: This study aims to analyze the effect of coal and biomass consumption on FABA generation during 2022, 2023, and 2024.Methods: The method employed is multiple linear regression using Minitab version 21.4.1 software, with coal consumption (X1) and biomass consumption (X2) as independent variables and FABA generation (Y) as the dependent variable.Result: The results show that coal consumption has a positive relationship with FABA generation, while biomass consumption shows a negative relationship. ANOVA test results indicate that only coal consumption significantly affects FABA generation. A notable decrease in FABA production in 2024 signifies an increase in biomass utilization in the fuel mixture, highlighting its potential in reducing solid waste generation from CFPP operations. A simulation involving three biomass-coal blending scenarios demonstrated that incorporating 20% biomass into the fuel mix can reduce FABA generation by up to 27.79%.